2010
DOI: 10.1007/s10512-010-9260-9
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy analysis of BN-600 power density calculations

Abstract: Methodological program techniques for performing neutron-physical calculations of fast-reactor cores with a description of the main codes TRIGEX, JARFR, GEFEST, MMKKENO, and ModExSys are described. The results of verification and assessment of the methodological errors on the basis of a test model of BN-600 are presented. Transport effects and mesh errors in the reaction rate distributions in the core, lateral screen, and in-reactor storage area are evaluated. An integral assessment of the computational accura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 3 publications
1
1
0
1
Order By: Relevance
“…The calculation and experiment discrepancies in the distributions of the 235 U and 239 Pu fission reaction rates in the steel radial blanket of a fast reactor at a level of 20 to 25% were recorded earlier in (Danilychev et al 2002;Kochetkov et al 2007;Mitenkova and Novikov 2011a). The results obtained in the study do not contradict to the calculation accuracies for the distributions of the power density field in a steel blanket evaluated earlier in (Blyskavka et al 2010;Mitenkova and Novikov 2011). An analysis of the BFS-66-B series experiments has however shown that a reduction in the calculation and experiment discrepancies to the measurement error level for the Cr 18% and Cr 28% steel grades can be explained by an overcompensati- on of errors in determining the Fe, Cr and Ni isotope neutron cross-sections.…”
Section: Analysis Of the Calculation Resultssupporting
confidence: 54%
“…The calculation and experiment discrepancies in the distributions of the 235 U and 239 Pu fission reaction rates in the steel radial blanket of a fast reactor at a level of 20 to 25% were recorded earlier in (Danilychev et al 2002;Kochetkov et al 2007;Mitenkova and Novikov 2011a). The results obtained in the study do not contradict to the calculation accuracies for the distributions of the power density field in a steel blanket evaluated earlier in (Blyskavka et al 2010;Mitenkova and Novikov 2011). An analysis of the BFS-66-B series experiments has however shown that a reduction in the calculation and experiment discrepancies to the measurement error level for the Cr 18% and Cr 28% steel grades can be explained by an overcompensati- on of errors in determining the Fe, Cr and Ni isotope neutron cross-sections.…”
Section: Analysis Of the Calculation Resultssupporting
confidence: 54%
“…Расчетно экспериментальные расхождения распределений скоростей реакций деле ния 235 U и 239 Pu в стальном боковом экране быстрого реактора, лежащие на уровне 20 -25%, отмечались ранее в [10 -12]. Полученные в работе результаты не противоречат ранее оцененным в [13] точностям расчета распределения поля энерговыделения в стальном экране. Однако анализ экспериментов серии БФС 66 Б показал, что снижение расчетно экспериментальных расхождений до уровня погрешности измерений для ста лей марки X18 и X28 может быть обусловлено перекомпенсацией ошибок в определе нии сечений изотопов Fe, Cr и Ni.…”
Section: результаты расчетовunclassified
“…was calculated using a Monte Carlo code(Blyskavka et al 2001, Zherdev et al 2018 with the BNAB-93 and BNAB-RF group neutron constants, as well as with evaluated neutron data files of the Russian ROSFOND library and versions of U.S., European and Japanese libraries from different years (ENDF, JEFF, JENDL).…”
mentioning
confidence: 99%